Realizing Justice for Conventional Media in Indonesia through Publisher Rights - Syafruddin; Syahriah, Rabiatul; Andre (Neoclassical Legal Review: Journal of Law and Contemporary Issues, 2023)
Digital platforms are currently posing a threat to conventional media's ability to remain sustainable. According to remarks made by President of the Republic of Indonesia Ir. H. Joko Widodo on February 11, 2023, during his working visit to Medan City in celebration of National Press Day, digital platforms account for 60% of media advertising spending in Indonesia. Regulations are therefore required to safeguard Indonesia's conventional media sector. The Press Council has taken the lead in proposing a Draft Presidential Regulation on the publisher's rights, or the responsibilities of digital platform companies in supporting quality journalism. the current draft law regarding publisher rights law in Indonesia and comparing it to the Canadian and Australian experience in the introduction of similar regulation.